Cytokines in sepsis: a critical review of the literature on systemic inflammation and multiple organ dysfunction - Vella, Roberta; Panci, Diego; Carini, Francesco; Malta, Ginevra; Vieni, Salvatore; David, Sabrina; Albano, Giuseppe Davide; Puntarello, Maria; Zerbo, Stefania; Argo, Antonina (Frontiers in Immunology, 2025)
Sepsis constitutes a profoundly heterogeneous and dynamic clinical syndrome, precipitated by a maladaptive host response to infection in which the immune system’s regulatory balance is fundamentally disrupted. The intricate interplay between proinflammatory and anti-inflammatory pathways, ordinarily responsible for maintaining immune homeostasis, becomes pathologically skewed. Within this altered immunological landscape, cytokines serve as pivotal mediators, orchestrating a cascade of cellular events that may culminate in a rapid transition from systemic hyperinflammation to a state of immune exhaustion or suppression. This review offers a critical synthesis of the current scientific literature on the immunopathogenesis of sepsis, with a particular emphasis on the molecular and cellular mechanisms governing cytokine regulation. Special attention is directed toward elucidating the contribution of these mediators to the onset and progression of multiorgan dysfunction syndrome (MODS), a central and often fatal complication of severe sepsis. Through an integrative examination of the principal immune signaling networks and pathophysiological processes involved in sepsis, this review provides a cohesive theoretical framework positioning immune dysregulation as the fundamental axis of clinical deterioration. Such an approach underscores the imperative for a deeper insight into the immunological architecture of sepsis, thereby laying the groundwork for the rational design of targeted, mechanism-based therapeutic strategies.